Biopolymer from Adenanthera pavonina L. Seeds: Characterization, Photostability, Antioxidant Activity, and Biotoxicity Evaluation - Roberta Cardoso Melo; Maurycyo Silva Geronço; Rayran Walter Ramos Sousa; Lara Polyana Silva Ramos; Francisca Pereira Araújo; Alessandra Braga Ribeiro; Paulo Michel Pinheiro Ferreira; Josy Anteveli Osajima; Marcília Pinheiro Costa (International Journal of Polymer Science)
Plant polysaccharides have been increasingly employed in the pharmaceutical, industrial, and food environments due to their versatile functional properties. In the present investigation, a heteropolysaccharide galactomannan (GAP) was extracted from Adenanthera pavonina L. seeds and characterized by physicochemical analyses to determine its thermal properties, photostability, antioxidant activity, and acute toxicity. GAP was characterized by FTIR, DSC, and TG. The photostability of GAP submitted to artificial UV irradiation was analyzed. Antioxidant activity was evaluated by the DPPH (2,2-diphenyl-1-1-picrylhydrazyl) free radical-scavenging method, while a bioassay method was carried out to study acute toxicity in Artemia salina L. Physical-chemical and functional characteristics of GAP support its potential role in the food and pharmaceutical industries. GAP was photostable under UV irradiation. In vitro GAP antioxidant evaluation showed that it bears free radical-scavenging activity for DPPH radicals. The median lethal concentration (LC50) of GAP was 239.4 mg∙mL−1, indicating that this biopolymer is nontoxic. Such results indicate that this biopolymer presents characteristics of neutrality, photostability, and nontoxicity that are commercially attractive.